2016
DOI: 10.15386/cjmed-627
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Different Oral Hygiene Aids for the Reduction of Morning Bad Breath Among Dental Students: A Crossover Clinical Trial

Abstract: Background and aimsTo assess and compare the effects of different oral hygiene procedures on the reduction of morning bad breath, plaque and gingival status in healthy subjects.MethodsA four step cross-over trial was performed on 32 study subjects. They were allocated into four groups: Group I: tooth brushing; Group II: tooth brushing and tongue scraping; Group III: tooth brushing and mouth washing; and Group IV: tooth brushing, tongue scraping and use of mouthwash. A washout interval of 7 days was employed. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
1
0
1
Order By: Relevance
“…Uses of mouthwash in conjunction with mechanical aids are effective in reducing plaque and gingival scores. 18 There is a difference in the relation between oral health and hygiene among students of students of dental medicine and students of other faculties. Munz et all 19 showed that the medical students had lower oral health-related and less positive attitudes about oral healthrelated behavior than the dental hygiene and dental students.…”
Section: Resultsmentioning
confidence: 99%
“…Uses of mouthwash in conjunction with mechanical aids are effective in reducing plaque and gingival scores. 18 There is a difference in the relation between oral health and hygiene among students of students of dental medicine and students of other faculties. Munz et all 19 showed that the medical students had lower oral health-related and less positive attitudes about oral healthrelated behavior than the dental hygiene and dental students.…”
Section: Resultsmentioning
confidence: 99%
“…Os compostos sulforados também podem ser mensurados com outros aparelhos como o Halímetro e o Breath Alert™, que é um monitor de sulfeto de menor porte e mais simplificado se comparado ao OralChroma, que apresenta seus resultados em escores. Estes aparelhores demonstraram ser capazes de diagnosticar a halitose assim como o método organoléptico, que é a técnica considerada o "padrão ouro" para tal análise (BRUNNER et al, 2010;OLIVEIRA-NETO et al, 2013;GODHA et al, 2016;FALCÃO et al 2017).…”
Section: Introductionunclassified